ENHANCING COMPETENCY MODEL FOR COUNSELLING TEACHERS IN HIGHER VOCATIONAL COLLEGES UNDER HENAN PROVINCE - Huixi, Zhang; Pruettikul, sataporn; Moonmuang, Sukhum (วารสารนิสิตวัง, 2025)
The objectives of this research were: (1) to explore the components of enhancing competence for counselling teachers in higher vocational colleges under Henan Province; (2) to develop competency model for counselling teachers in higher vocational colleges under Henan Province; and (3) to propose guidelines of enhancing competence for counselling teachers in higher vocational colleges under Henan Province. The population included 747 counselling teachers from five higher vocational colleges under Henan Province. The sample size was determined by Krejcie and Morgan’s Table, obtained by stratified random sampling technique, totaling 287, and the nine key informants were selected by purposive sampling method, who were deans and counselling leaders’ teachers in higher vocational colleges under Henan Province for interview and focus group discussion. The instruments used for data collection included a semi-structured interview form, a five-point rating scale questionnaire, and Focus Group Discussion form. The statistics used for data analyzed were descriptive statistics and Exploratory Factor Analysis. The research found that: (1) there were five components of enhancing competence of counsellors in higher vocational colleges in Henan Province which consisted of Vocational knowledge and Ideology, Occupation or Career Guidance, Cross–Disciplinary knowledge, Activity on Students affairs Management, and Supported Innovation and Technology; (2) the enhancing competence for counselling teachers in higher vocational colleges under Henan Province was the “VOCAS Model”; and (3) there were three guidelines followed the VOCAS model of enhancing competence for counselling teachers in higher vocational colleges under Henan Province namely; Competency-Based Professional Development Program for counselling teachers, Collaborative Learning and Innovation Practice for enhancing on technical and skill of counselling teachers, and Mentoring, Monitoring, and Continuous Improvement on counselling teachers.